Modelling the Effect of Digital Financial Inclusion on Income Inequality in Developing Countries - Savandha, Septien Dwi (Sekolah Tinggi Agama Islam Kuningan, 2025)
Income inequality remains an urgent issue in developing countries, which can hinder economic growth and social stability. In the last decade, digital financial inclusion has grown rapidly as a potential solution to narrow this gap by opening up access to financial services for previously unreachable communities. This study aims to analyze the effect of digital financial inclusion on income inequality in developing countries, focusing on the potential of financial technology in narrowing economic gaps. Using econometric methods with panel data from several developing countries for the period 2015 to 2023, this model measures the impact of access to digital financial services on the distribution of people's income. The data used included variables related to digital payment adoption, mobile financial service usage, and access to digital credit, which were analyzed using the dynamic panel regression method. The results show that increasing digital financial inclusion has a significant negative correlation with income inequality. This indicates that access to digital financial services can encourage income equity by providing a wider means of economic inclusion. These findings have important implications for policymakers in designing digital financial strategies to support more inclusive economic stability